Assembly and Annotation of Transcriptome Provided Evidence of miRNA Mobility between Wheat and Wheat Stem Sawfly - Cagirici, Halise B.; Biyiklioglu, Sezgi; Budak, Hikmet (Frontiers in Plant Science, 2017)
Wheat Stem Sawfly (WSS), Cephus Cinctus Norton (Hymenoptera: Cephidae), is one of the most important pests, causing yield and economic losses in wheat and barley. The lack of information about molecular mechanisms of WSS for defeating plant’s resistance prevents application of effective pest control strategies, therefore, it is essential to identify the genes and their regulators behind WSS infestations. Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) are recognized with their regulatory functions on gene expression, tuning protein production by controlling transcriptional and post-transcriptional activities. A transcriptome-guided approach was followed in order to identify miRNAs, lncRNAs and mRNA of WSS, and their interaction networks. A total of 1,893 LncRNAs were presented here as differentially expressed between larva and adult WSS insects. There were 11 miRNA families detected in WSS transcriptome. Together with the annotation of 1,251 novel mRNAs, the amount of genetic information available for WSS was expanded. The network between WSS miRNAs, lncRNAs and mRNAs suggested miRNA-mediated regulatory roles of lncRNAs as competing endogenous RNAs. In the light of the previous evidence that small RNA molecules of a pathogen could suppress the immune response of host plant, we analyzed the putative interactions between larvae and wheat at the miRNA level. Overall, this study provides a profile of larva and adult WSS life stages in terms of coding and non-coding elements. These findings also emphasize the potential roles of wheat and larval miRNAs in wheat resistance to infestation and in the suppression of resistance which is critical for the development of effective pest control strategies.